Effects of size quantization in the spectra and Γ − M transitions in (GaAs)m(AlAs)n(001) superlattices; Physica E: Low-dimensional Systems and Nanostructures; Vol. 103 - Grinyaev S. N. Sergey Nikolaevich (2018, 2018)
Title screen